TBIO-15. UTILIZING A HISTOLOGY-SPECIFIC SEQUENCING ALGORITHM FOR PRECISION NEURO-ONCOLOGY. Issue 2 (22nd June 2018) - Rajappa, Prajwal; Maachani, Uday; Bareja, Rohan; Wang, Kenneth; Sboner, Andrea; Hoffman, Caitlin; Souweidane, Mark; Elemento, Olivier; Pisapia, David; Greenfield, Jeffrey
Abstract: INTRODUCTION: Given extreme tumor variability and heterogeneity in pediatric neuro-oncology, combined with often dismal prognosis for inoperable and recurrent tumors, advanced sequencing (NGS) platforms are now commonly employed to identify clinically relevant targets to augment the current standard of care. METHODS: Resected tumor tissue and blood from a histologically diverse patient cohort (n=53) was allocated for various genomic platforms including whole exome sequencing (WES), RNA sequencing, and methylation profiling. If no clinically actionable alterations were found with WES, deeper sequencing was performed at the gene expression level through RNA sequencing and fusion analyses. Methyl capture (RRBS) was utilized to delineate the epigenetic landscape for discreet glial tumors such as ependymomas, high grade gliomas and infiltrative tumors such as DIPG and gliomatosis cerebri (GC). RESULTS: 20% of somatic alterations detected from WES had clinical utility which includes the definition of a targetable mutation or fusion, helping pathology define a specific diagnosis, aiding a clinical team in providing prognosis to a family or facilitating an N of 1 clinical trial with a patient with recurrent or inoperable CNS disease. CONCLUSION: We have attempted to refine a streamlined and personalized sequencing approach to enhance our ability to eliminate indecision over competing sequencing platforms based on tumor location, and frozen pathology. This has allowed us to deliver actionable, diagnostic and clinically relevant information to treating neuro-oncology teams at a reasonable cost and speed, while serving as a platform to consider more frequent utilization of n of 1 clinical trials.